The influence of organizational citizenship behaviour and islamic spirituality on organizational effectiveness in the higher educational institutions - Mohammad Wildan Shohib (Kulliyyah of Education, International Islamic University, 2021)
The purpose of this study is to examine the influence of organizational citizenship behavior (OCB) and Islamic spirituality (IS) on organizational effectiveness (OE) through the mediating variable of organizational climate (OC) as perceived by academic staff in selected state Islamic higher education institutions in Indonesia. This study employed 357 academic staff who completed a questionnaire survey out of the 450 targeted distributions to academic staff through six selected Indonesian state Islamic higher education institutions. The statistical analysis techniques utilized in this study were Descriptive Analysis using SPSS version 22.0, Confirmatory Factor Analysis (CFA) and full-fledge Structural Equation Modelling (SEM) using the software Analysis of Moment Structures (AMOS) version 22.0 to address the research questions as well as to test the research hypotheses. Based on the results of CFA, it demonstrates that four distinct factors present the construct of perceived organizational citizenship behavior. In contrast, the construct of Islamic spirituality also presents four diverse factors. Moreover, the mediating variable of organizational climate was explained by two distinct factors, while three discrete factors described the construct of organizational effectiveness. This study found that Islamic spirituality and organizational climate have a direct causal effect on organizational effectiveness. The generated results of the study also indicate that organizational citizenship behavior and Islamic spirituality have indirect causal effects on organizational effectiveness through the mediating variable of organizational climate. Further analysis, however, shows that only organizational citizenship behavior does not have a direct causal effect on organizational effectiveness in the context of selected state Islamic higher education institutions. Theoretically, the study suggests that the university top management should not consider teaching qualification as the only criterion in hiring academic staff but should ponder on other potentials such as the quality of HRM. Implications from the result of the study propose that university top leaders should organize a human resource development program for academic staff to educate them about quality assurance. This study significantly assist the human resource managers and executive leaders in obtaining the best practices of OCB, IS and OC influencing OE in HEIs. Moreover, the findings suggest that Islamic spirituality as a sense of totality, connectedness at work, and greater ethics and moral values that should be inculcated among academic staff in the university. Finally, the study recommends more examinations on underlying constructs to develop the best model of organizational effectiveness in HEIs.